2014
DOI: 10.1002/aur.1375
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know About Suicidality in Autism Spectrum Disorders? A Systematic Review

Abstract: Suicidality is a common and concerning issue across development, and there is a plethora of research on this topic among typically developing children and youth. Very little is known, however, about the nature of suicidality among individuals with autism spectrum disorders (ASDs). The purpose of the current study was to undertake a systematic literature review to assess the current state of the research literature to examine the prevalence of suicidality among individuals with ASD, related demographic and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(109 citation statements)
references
References 66 publications
(164 reference statements)
6
101
0
2
Order By: Relevance
“…It can be concluded that children and adolescents with high functioning ASD have a higher risk of suicide compared to their typically developing peers. The result of our study reconciles with results of previous studies which reported a high rate of suicidality in groups with a diagnosis of ASD 1417…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It can be concluded that children and adolescents with high functioning ASD have a higher risk of suicide compared to their typically developing peers. The result of our study reconciles with results of previous studies which reported a high rate of suicidality in groups with a diagnosis of ASD 1417…”
Section: Discussionsupporting
confidence: 92%
“…Recently, two reviews were published on this topic 16,17. First Hannan and Taylor’s review of four different studies revealed that prevalence of suicidality among adolescents and young adults with ASD varied from 7% to 42% 16.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the ICD E-codes 950–959 include both self-inflicted injury with and without suicidal intent so we are unable to precisely sort out suicidal intent for specific visits. Nevertheless, this is the third study to report these findings for self-inflicted injury (Schelnz et al, 2015; McDermott et al, 2008), which converges with increasing concern in the literature and media about suicidal behavior in youth with ASD (Segers & Rawana, 2014; Hannon & Taylor, 2013). Many pediatric emergency department physicians, however, are unfamiliar with the best course of action for individuals with ASD or ID who are deemed to be at high risk.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, findings cannot be generalised with confidence, and additionally most study samples are small in size, and very few have drawn comparisons with the general population. It has been suggested that depression,3 bipolar disorder,4 suicidal thoughts/behaviour,5 non-affective psychosis6 and attention-deficit hyperactivity disorder7 8 may be more common in adults with autism. A further study in North California, USA used medical records from a single health delivery provider of inpatient and outpatient medical and mental health services to identify 1507/1 578 658 (0.1%) adults with autism, who were age and gender matched with controls without recorded autism 9.…”
Section: Introductionmentioning
confidence: 99%